Case Report: Liquid-based cytology diagnosis of pulmonary mucormycosis - Shuai Luo; Xiaoxue Tian; Ting Xu; Yao Li; Qing Ji; Jinjing Wang (Frontiers in Medicine, 2025)
BackgroundMucormycosis is an infrequent yet life-threatening opportunistic fungal infection, typically secondary to diabetic ketoacidosis. Owing to its non-specific clinical presentation and auxiliary test findings, timely diagnosis remains difficult. While fungal culture, direct smear, histopathological biopsy, and molecular diagnostic techniques are available, cytological evaluation and histopathological biopsy remain the principal modalities in clinical settings. Notably, cytological identification of mucorales remains rare.Case presentationA 41-year-old male presented with a 20-day history of productive cough and fever, accompanied by a recent onset of hemoptysis. His medical history included type 2 diabetes mellitus. Diagnostic confirmation of mucormycosis was achieved through conventional cytological smear, liquid-based cytology, cell block preparation, tissue biopsy, and specialized staining techniques. Pulmonary mucormycosis was ultimately diagnosed.ConclusionThis report documents a case of pulmonary mucormycosis identified via conventional cytological smear, liquid-based cytology, and cell block preparation. Liquid-based cytology and cell block techniques offered a non-invasive and more expedient approach, highlighting their value in the early identification and intervention of mucormycosis.